The health economics of Aflatoxin: Global burden of disease - Wu, Felicia; Narrod, Clare A.; Tiongco, Marites; Liu, Yanyan (International Food Policy Research Institute, 2011)
In 2004, several hundred Kenyans became severely ill, and 125 died, of acute aflatoxicosis: a disease of liver failure associated with consuming extremely high levels of aflatoxin in food (Lewis et al. 2005; Strosnider et al. 2006). Since then, over the last six years, greater global public attention has been drawn to aflatoxin and its associated health risk.